1999
DOI: 10.1103/physrevlett.82.4795
|View full text |Cite
|
Sign up to set email alerts
|

Charge Equilibration Time of Slow, Highly Charged Ions in Solids

Abstract: We report observations of nonequilibrium charge state distributions of slow, highly charged ͑331 # q # 751͒ ions after transmission of thin carbon foils. Charge equilibration times are determined directly from the dependencies of exit charge states on projectile velocity ͑0.5 3 10 6 , y , 10 6 m͞s͒ and foil thickness (5 -10 nm). Ions like Xe 441 and Au 681 are found to equilibrate inside of solid matter in a time of only 7 fs. [S0031-9007(99)09368-0]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…This value is of the same order as the typical excitation times for an electron-hole pair of eV separation as well as the response time of the electron gas to screen the projectile. Very recently, Hattass et al [20] have found comparably short charge equilibration times (7 fs) for, e.g., Th 651 penetrating 5 nm C foils. Shorter interaction times are crucial to study effects which are present in the preequilibrium range only: Juaristi et al [21] investigated the dependence of the electronic stopping on projectile L-and K-shell vacancies on a 10 fs time scale.…”
Section: Kvi Atomic Physics Rijksuniversiteit Groningen Zernikelaanmentioning
confidence: 98%
“…This value is of the same order as the typical excitation times for an electron-hole pair of eV separation as well as the response time of the electron gas to screen the projectile. Very recently, Hattass et al [20] have found comparably short charge equilibration times (7 fs) for, e.g., Th 651 penetrating 5 nm C foils. Shorter interaction times are crucial to study effects which are present in the preequilibrium range only: Juaristi et al [21] investigated the dependence of the electronic stopping on projectile L-and K-shell vacancies on a 10 fs time scale.…”
Section: Kvi Atomic Physics Rijksuniversiteit Groningen Zernikelaanmentioning
confidence: 98%
“…We note that these chemical methods can also be employed while target ionization is maximized. Highly charged ions with keV energies deposit their potential energy (the sum of the binding energies of the electrons that were removed when forming the ion) within about 10 fs, close to the target surface [15]. This fast charge equilibration constitutes an energy deposition rate matched only by MeV/u heavy ions, or heavy clusters with MeV energies.…”
Section: Interaction Of Highly Charged Ions With Solidsmentioning
confidence: 99%
“…In contrast, the high density of electrons in antibonding states created by an intense, ultra-fast electronic excitation can impart an impulse leading to atomic displacements [9][10][11][12]. Direct evidence of atomic motion on a ∼160-fs time scale due to antibonding state excitation is reported by Petek et al [13].The deposition of potential energy from slow, highly charged ions (SHCI) such as Xe 44+ (616-keV kinetic energy in this study) in semiconductor surfaces forms highly localized regions of intense electronic excitation [10,14] on femtosecond time scales [15]. We define slow ions as ions with velocities less than the Bohr velocity.…”
mentioning
confidence: 90%
“…The deposition of potential energy from slow, highly charged ions (SHCI) such as Xe 44+ (616-keV kinetic energy in this study) in semiconductor surfaces forms highly localized regions of intense electronic excitation [10,14] on femtosecond time scales [15]. We define slow ions as ions with velocities less than the Bohr velocity.…”
Section: Introductionmentioning
confidence: 99%